Tietz fundamentals of clinical chemistry and molecular diagnostics - Burtis, Carl A. (Elsever, 2015)
A condensed, easier-to-understand student version of the acclaimed Tietz Textbook of Clinical Chemistry and Molecular Diagnostics, Tietz Fundamentals of Clinical Chemistry and Molecular Diagnostics, 7th Edition uses a laboratory perspective in providing the clinical chemistry fundamentals you need to work in a real-world, clinical lab. Coverage ranges from laboratory principles to analytical techniques and instrumentation, analytes, pathophysiology, and more. New content keeps you current with the latest developments in molecular diagnostics.